2018
DOI: 10.1104/pp.17.01537
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of the Arabidopsis Replication Timing Program

Abstract: 33Eukaryotes use a temporally regulated process, known as the replication timing program, to 34 ensure that their genomes are fully and accurately duplicated during S phase. Replication timing 35 programs are predictive of genomic features and activity, and considered to be functional 36 readouts of chromatin organization. Although replication timing programs have been described 37 for yeast and animal systems, much less is known about the temporal regulation of plant DNA 38 replication or its relationship to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 91 publications
7
35
0
Order By: Relevance
“…In middle S phase, replication was almost evenly dispersed along the entire chromosomes and only slightly increased in the interstitial regions of chromosome arms. These findings confirmed the recent results made in Arabidopsis and maize obtained by Repli-seq analysis and corresponded to the gene density of their chromosome profiles (Wear et al , 2017, Zynda et al , 2017; Concia et al , 2018). Kwasniewska et al (2018) showed that terminal parts of barley chromosomes replicated in early S phase, whole chromosomes were covered with EdU signal at middle S phase and centromeric parts of chromosomes were replicated in late S phase.…”
Section: Discussionsupporting
confidence: 91%
“…In middle S phase, replication was almost evenly dispersed along the entire chromosomes and only slightly increased in the interstitial regions of chromosome arms. These findings confirmed the recent results made in Arabidopsis and maize obtained by Repli-seq analysis and corresponded to the gene density of their chromosome profiles (Wear et al , 2017, Zynda et al , 2017; Concia et al , 2018). Kwasniewska et al (2018) showed that terminal parts of barley chromosomes replicated in early S phase, whole chromosomes were covered with EdU signal at middle S phase and centromeric parts of chromosomes were replicated in late S phase.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, studies comparing chromatin regions with different replication timing patterns in maize root tip nuclei showed that open chromatin and densely packed heterochromatin domains tend to be duplicated in early and late S phases, respectively [61,62]. The same correlation was seen in Arabidopsis suspension cells, that repressed chromatin were enriched in late replicated loci [63,64]. Further, live imaging of Arabidopsis replisomes revealed their dynamic distribution in early and late S phase [65].…”
Section: Dna Replication Timingmentioning
confidence: 73%
“…Use of relatively unexplored organisms for studying replication is also effective, especially when one focuses on unique developmental stages. Due to the availability and feasibility of NGS, non-mammalian organisms without much information about DNA replication regulation have recently been utilized for genome-wide DNA replication studies, including chicken [76,77], zebrafish [78], Caenorhabditis elegans [79], maize [80], Arabidopsis [81], Drosophila [82] and others [83,84]. In particular, DNA replication profiling during early zebrafish embryogenesis demonstrated the presence of a DNA replication timing program prior to the mid-blastula transition (MBT) [78].…”
Section: Unraveling the Complex Relationship: Replication Timing mentioning
confidence: 99%